WU-CART-007, an Allogeneic CAR T-Cell Targeting CD7 in Relapsed/Refractory (R/R) T-Cell Acute Lymphoblastic Leukemia/Lymphoma (T-ALL/LBL): Phase 2 Results - Aldoss, Ibrahim; Ghobadi, Armin; Maude, Shannon L.; Bhojwani, Deepa; Wayne, Alan S.; Bajel, Ashish; Dholaria, Dr. Bhagirathbhai; Faramand, Rawan; Mattison, Ryan J.; Rijneveld, Anita; Zwaan, C. Michel; Calkoen, Friso; et al. (Transplantation and cellular therapy, 2025)
R/R T-ALL/LBL are difficult-to-treat malignancies with limited options. WU-CART-007 is a CD7-targeted CAR T-cell product with CRISPR/Cas9 deletion of CD7 and TRAC, preventing fratricide and enabling allogeneic T-cell use (Leedom et al., ASH 2021). We present updated time-to-event (TTE) data from the Phase 2 portion of WU-CART-007 1001 (NCT04984356) in R/R T-ALL/LBL patients. Patients in phase 2 received a single infusion of 900 million WU-CART-007 cells on Day 1 following lymphodepleting chemotherapy (fludarabine 30 mg/m2/day x 4 days and cyclophosphamide 1000 mg/m2/day x 3 days). Disease response was assessed by Day 28 bone marrow (BM) assessment and CT/PET, if applicable. Composite complete remission (CRc) included CR (BM blasts <5%, absolute neutrophil count ≥1,000/μL, platelets ≥100,000/μL) and CRi (CR with incomplete recovery), with SUV uptake below liver/mediastinum in extramedullary disease (EMD). Objective response rate (ORR) included CRc and partial response (reduced EMD uptake). Duration of response (DOR) was from initial response to relapse or death, and TTE endpoints were analyzed using Kaplan-Meier statistics. As of 24 Jul 2024, 13 patients had been dosed, median age 23 years (range 14-47). They had a median of 5 prior therapies (range 1-9); 46% (6/13) with prior allo-HSCT. Baseline disease burden included EMD in 38.4% (5/13) of patients and 8/13 with BM disease with median BM blasts of 82.5% (range 5-95%). Treatment-related adverse events ≥ Grade 3 occurred in 77% (10/13). Cytokine Release Syndrome (CRS) was observed in 100% (13/13), mostly Grade ≤ 2 (69%); four (31%) had ≥ Grade 3, managed with steroids (75%), tocilizumab (100%), anakinra (25%). One (8%) Grade 1 immune effector cell-associated neurotoxicity event was reported. Severe (≥ G3) infections were seen in 46% (6/13), including sepsis (31%) and opportunistic infections. Two Grade 5 events occurred: one due to fungal sepsis on Day 13, and another from multi-organ failure with Grade 3 CRS and disease progression on Day 7. Among all evaluable pts, ORR was 91% (10/11), and CRc was 73% (8/11; 6 CR, 2 CRi). Patients with CRc and available MRD data were 83% (5/6) MRD negative. Five subjects went on to allo-HSCT. With follow-up up to 9.9 months, the median DOR was not reached (95% CI: 0.5, NE; range 0.5-9.1 m); 4 pts remain in continuous CR at 9.1, 8.2, 6.7, and 6.7 months. EMD patients had an ORR of 80% (4/5; 2 CR, 2 PR). Partial responders had a reduction in disease burden of 78.5 and 95.7 by Lugano Criteria. WU-CART-007 demonstrated anti-leukemic activity with an acceptable safety profile in heavily pre-treated R/R T-ALL/LBL pts. A follow-up study (NCT06514794) including patients > 1 year old and an exploratory MRDpos cohort will begin enrolling in late 2024.